Multilingualism in academic and educational constellations - Sudhoff, Stefan 1977-; Thije, Jan D. ten 1955- (Mehrsprachigkeit, 2024)
The contributions of this book underpin the fact that multilingualism is a stimulus for the acquisition of more linguistic knowledge by individuals or groups of language users as well as an engine of scientific knowledge expansion as such. The book begins with the analysis of overarching socio-political developments and, through the introduction of new theoretical linguistic concepts and the educational practices of academic writing, concludes with the microanalysis of linguistic procedures.